2021
DOI: 10.1016/j.ejca.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The concepts of rechallenge and retreatment with immune checkpoint blockade in melanoma patients

Abstract: Forty to 60% of patients with advanced or metastatic melanoma respond to firstline immune checkpoint inhibitors (ICI) and half of all patients in the metastatic setting eventually progress. This review evaluated the latest long-term data from clinical trials. It also considered data from recent retrospective studies, as these address important questions for clinical practice. 'Retreatment' defined as 'repeated treatment with the same therapeutic class following relapse after adjuvant treatment has ended' and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…While re-induction of ICB has not been investigated in metastatic UM to the authors' knowledge, re-induction of ICB was performed in a panel of other cancer entities including CM [17]. In one retrospective multicenter study, patients with advanced CM who initially achieved at least a sustained SD to combined ICB and then progressed were re-inducted with ipilimumab alone or in combination with anti-PD-1, yielding an ORR of 26% (12/47) and a DCR of 45% (21/47) [12].…”
Section: Discussionmentioning
confidence: 99%
“…While re-induction of ICB has not been investigated in metastatic UM to the authors' knowledge, re-induction of ICB was performed in a panel of other cancer entities including CM [17]. In one retrospective multicenter study, patients with advanced CM who initially achieved at least a sustained SD to combined ICB and then progressed were re-inducted with ipilimumab alone or in combination with anti-PD-1, yielding an ORR of 26% (12/47) and a DCR of 45% (21/47) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to rechallenge or subsequent therapies are being explored for those patients who eventually progress following ICB. Rechallenge regimens utilize repeated treatments with the same therapeutic class of drug following disease progression in patients who experienced previous clinical benefit with prior treatment for unresectable or metastatic disease ( 54 , 54 ). This is typically considered because there are few effective treatment options for melanoma after progression on ICB.…”
Section: Icb Treatment Rechallengementioning
confidence: 99%
“…These antibodies target negative regulators of T cell activation to prevent them from being activated, thus resulting in prolonged T cell activation in the tumor and enhanced antitumor response. About 50% of melanoma patients with advanced or metastatic disease have durable responses to ICB [ 78 , 79 ]. Despite the success that multiple immunotherapeutic agents have had on the survival of melanoma patients, there is an important subset of patients who develop resistance or whose disease progresses after these therapies.…”
Section: Role Of Epigenetics In Resistance To Targeted Therapies and Immunotherapymentioning
confidence: 99%
“…Treatment-related adverse events are reported more frequently in ipilimumab-treated patients compared to nivolumab-treated patients [ 79 , 116 ]. However, a clinical trial demonstrated that the combination of guadecitabine and ipilimumab was safe in patients with unresectable stage III/IV melanoma and that it upregulates HLA class I in melanoma cells and enhances antitumor immunity as demonstrated by an increase in CD8+ PD-1+ T cells and CD20+ B cells [ 117 ].…”
Section: Epigenetic Modifiers As Therapeutic Adjuvants For Melanoma Patientsmentioning
confidence: 99%